Expression and significance of laminin receptor in squamous cell carcinoma of the tongue. (11th October 2021) - Matsuo, Katsuhisa; Akiba, Jun; Ogasawara, Sachiko; Kondo, Reiichiro; Naito, Yoshiki; Kusano, Hironori; Sanada, Sakiko; Kakuma, Tatsuyuki; Kusukawa, Jingo; Yano, Hirohisa
Abstract: Background: Laminin receptor is a non‐integrin cell‐surface receptor that binds laminin present on the basement membrane. It has been reported to be associated with infiltration and metastasis of various malignant tumors. However, no studies regarding tongue cancer have been reported. This study aimed to clarify the role of laminin receptor in squamous cell carcinoma of the tongue. Methods: We performed immunohistochemical staining of specimens from 66 patients with squamous cell carcinoma of the tongue and assessed laminin receptor expression and clinicopathological factors. As epithelial‐mesenchymal transition has been shown to be associated with infiltration and metastasis of malignant tumors, staining for E‐cadherin, vimentin, and N‐cadherin were also performed. Results: Of 20 patients with postoperative recurrence, 14 exhibited high laminin receptor expression ( p = 0.0025). Kaplan‐Meier analysis revealed a significantly shorter time to postoperative recurrence for the high laminin receptor expression group than that for the low laminin receptor expression group ( p = 0.0008). Based on multivariate analyses for postoperative recurrence, high laminin receptor expression was associated with poor prognosis (high expression vs. low expression; HR =3.19, 95% CI =0.92–11.08; p = 0.0682). There was a correlation between laminin receptor and N‐cadherin ( p = 0.0089) but not between laminin receptor and E‐cadherin ( p = 0.369) or vimentin ( p = 0.4221). Conclusion: These results suggest that high laminin receptor expression is a useful prognostic factor for postoperative recurrence and may be a target for molecular therapy to treat squamous cell carcinoma of the tongue.